Pairwise correlations - CHORDIA, Tarun (Institutional Knowledge at Singapore Management University, 2011)
Pairwise stock correlations increase by 27% on average when stock returns are negative. It is trading activity in small stocks that leads to higher correlations when returns are negative. We provide evidence consistent with the hypothesis that co-ordinated selling by retail investors drives this asymmetry in correlations. The co-ordinated selling activity by retail investors is triggered by negative market returns.